2021
DOI: 10.1186/s12968-021-00771-y
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow dynamics with four-dimensional flow cardiovascular magnetic resonance in patients with aortic stenosis before and after transcatheter aortic valve replacement

Abstract: Background Pre- and post-procedural hemodynamic changes which could affect adverse outcomes in aortic stenosis (AS) patients who undergo transcatheter aortic valve replacement (TAVR) have not been well investigated. Four-dimensional (4D) flow cardiovascular magnetic resonance (CMR) enables accurate analysis of blood flow dynamics such as flow velocity, flow pattern, wall shear stress (WSS), and energy loss (EL). We sought to examine the changes in blood flow dynamics of patients with severe AS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
(72 reference statements)
1
11
0
Order By: Relevance
“…39,40 The blood flow patterns vary between TAVI, the surgical aortic valve replacement, and the natural valve, which could affect pressure recovery. 41,42 Thus, current data of echo-Doppler gradients in TAVI should be corroborated because of the unique designs of TAVI. Niderberger et al 39 used a pulsatile model to exhibit the degree of pressure recovery.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 The blood flow patterns vary between TAVI, the surgical aortic valve replacement, and the natural valve, which could affect pressure recovery. 41,42 Thus, current data of echo-Doppler gradients in TAVI should be corroborated because of the unique designs of TAVI. Niderberger et al 39 used a pulsatile model to exhibit the degree of pressure recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac magnetic resonance (CMR) is apt in this respect, as it provides accurate structural measurements while also revealing tissue properties and even hemodynamic patterns. 16,17 Tissue fibrosis, of note, has been correlated with both symptoms and prognosis in AS. 1 Valvulo-arterial impendence is another measure that may gauge the whole syndrome of AS by intentionally accounting for the interaction among ventricle, valve, and vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] A few in vitro studies reported a substantial impact of actual THV frame geometry (eccentricity/non-round shape and under-expansion) on the altered trans-valvular ow characteristics. [6][7][8][9][10] Large eld-of-view intravascular ultrasound (IVUS) offers a unique tomographic perspective for a direct peri-procedural measure of THV stent frame and lea et geometry. [11][12][13][14][15] We compared the peri-procedural IVUS assessment of SAPIEN 3 THV expansion deployed during VIV transcatheter mitral (TMVR) or tricuspid valve replacement (TTVR) versus the post-procedural multislice computed tomography (MSCT) and assessed the correlation between THV dimensions in MSCT and predischarge transvalvular gradients.…”
Section: Introductionmentioning
confidence: 99%